Sistemas de deshije con el método de selección de yemas en una plantilla de banano musa sapientum v. cavendish en El Guabo - Heredia Quezada, Cristina Marisela (2013)
On the farm "Envy", located Palestina to the parish Barbones belonging, city the Guabo province of El Oro, research was conducted on five types of suckering. The objectives were: 1.Determine the difference in vegetative development of the second and third selected a template yolk banana. 2. Set the height of the child-yolk to emergency 120 days of each treatment. The materials used were a staff of Cavendish bananas, machete, lampilla pencil note book, calculator, printer and computer. The treatments were: T1 16 weeks1 egg yolk satellite center in 2nd with pseudostem, T2 16 weeks 2 yolks satellite central pseudostem 2nd; T3 plants 16 weeks 1 egg yolk with the 3do satellite pseudostem; T4 16 weeks 2 yolks power the satellite 3do pseudostem and T5 with 1 egg yolk 16 with out pseudotallo, the 2nd satellite variables studied in the present investigation are as follows: Height of bud sat 30, 45, 60 and 90 days of selection, number of functional leave sat 90 days, percentage of functional root sat 90 days, leaf area at 120 days, number of leaves at 120 days, and thickness to the appearance pseudostem. This study was conducted on a staff of two hectares of Cavendish banana variety sown 16 weeks was chosen an area of 10.000 m2 which is divided in to two lots with 30 rows of plants each, were chosen 10 plants per each treatment and the sprite paint marking identified the pseudostem for making data respectively. In week 20 we proceeded to desuckering respective indicating to the witness took the first satellite buds and leave a bud second satellite in the other 10 plants selected and eliminated two chose them by force and position. For desuckering took the lampilla which serves to remove yolks and no harm to the plant.